PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MUATAN PPKn KELAS V DI SDN 147/VIII BOGO REJO KABUPATEN TEBO - Amril; Sri Yunimar Ningsih; Sri Marlina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study is to develop animated video learning media products for PPKn content in class V SDN 147/VIII Bogo Rejo, Tebo Regency. The product developed is in the form of animated video learning media. There is a research objective because there are several problems at SDN 147/VIII Bogo Rejo in PPKN content in class V, namely the absence of teachers developing learning animation video media especially for videos, the two teachers find it difficult in developing media at school, the three students are less interested in the learning process especially PPKn content because PPKn learning has a lot of lectures or stories. This study uses the ADDIE Research and Development (R&D) model which has 5 sections, namely: Analysis, Design, Development, Implementation, Evaluation. Types of data in the form of quantitative and qualitative data. The data collection instruments are validity, practicality and effectiveness. Data collection techniques were data on the validity of animated video learning media, data on the practicality of animated video learning media and data on the effectiveness of animated video learning media. The analysis technique used uses validity, practicality and effectiveness. The use of products developed in teaching and learning activities at SDN 147/VIII Bogo Rejo, Tebo Regency is able to improve student learning outcomes, especially in material 1, the diversity of national cultures in the Indonesian region, material 2, attitudes towards the diversity of types of community businesses, and material 3, learning tolerance from games. traditional children. This is in accordance with the results of the effectiveness test conducted that out of 15 who took part in learning using the media developed in material 1 it was stated that 80% completed material 2 which was stated to be 86.6% complete and material 3 was obtained 86.6% complete.